Pengaruh Total Quality Management dan ISO 9001 : 2000 terhadap Kinerja Perusahaan Jasa Konstruksi di Jawa Timur - Iwan Tjahjo Santoso; Djumilah Zain; Mintarti Rahayu; Munawar Ismail (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
There is a different opinion in the application of TQM and ISO 9001 : 2000 as a quality management system on business performance. In one side the system is considered successful in improving company business performance; but in another side it is said not to give contribution in the improvement of business performance. Meanwhile, in this globalization era the demand of high quality makes business more competitive. The research was conducted at construction service corporations by using primary and secondary data. The result proves that there are 3 important findings : Firstly, ISO Effort does not directly influence Business Performance. On the other hand, indirectly ISO Effort through Competitiveness turns out to influence the improvement of Business Performance. The better ISO Effort, the greater its contribution to the improvement of Competitiveness consisting of such components as cost, quality, delivery, flexibility and ultimately it gives significant contribution to the improvement of Business Performance. Secondly it proved that Competitiveness gives the biggest contribution to Business Performance. This shows that Competitiveness still shows its important role in the meeting the target to get construction service projects. Thirdly, TQM Practice directly or indirectly, through Competitiveness, is proved to significantly influence Business Performance. In addition, ISO Effort, through TQM Practice is also proved indirectly influence Business Performance. Therefore, it can be said that ISO Effort is a foundation or an initial step towards TQM Practice in forming strong quality culture. Furthermore, good TQM Practice plays an important role both directly and indirectly in the improvement of Business Performance.Keywords: TQM Practice, ISO Effort, Competitiveness, Construction Services